Sensory and Analytical Evaluations of Paints With and Without Texanol - Gallagher, Michelle; Dalton, Pamela; Sitvarin, Laura; Preti, George (Environmental science & technology, 2008)
Perception of odor can figure prominently in complaints about indoor air, yet identification of the responsible compound(s) is often difficult. For example, paint emissions contain a variety of odorous volatile organic compounds (VOCs) which may trigger reports of irritation and upper respiratory health effects. Texanol ester alcohol (2,2,4-trimethyl-1,3-pentanediol monoisobutyrate), a paint coalescing agent, is frequently associated with the “persistent, characteristic odor” of water-based paint. To evaluate the sensory impact of Texanol, naïve (unfamiliar with paint constituents) and experienced (familiar with paint constituents) subjects evaluated the odor properties of paints with and without Texanol. VOC emissions from neat paint and paint applied to gypsum wallboard were collected via solid-phase microextraction and analyzed by gas chromatography/mass spectrometry and gas chromatography/olfactometry. Regardless of subjectsʼ prior experience, aromatic hydrocarbons and oxygenated compounds, introduced from other paint additives and not Texanol, were most commonly associated with paint odor. However, quantitative sensory techniques demonstrated that addition of Texanol to paints led to an overall increase in the perceived intensity of the coating. The combined use of these techniques proved to be an effective methodology for analyzing the structure of paint volatiles and their sensory properties and holds promise for solving many odorous indoor air problems.